Catalog of Andreev spectra and Josephson effects in structures with time-reversal-invariant topological superconductor wiresCentro Internacional de Estudios Avanzados - Arrachea, Liliana del Carmen; Camjayi, Alberto; Aligia, Armando Angel; Gruñeiro, Leonel José (American Physical Society, 2019)
Fil: Arrachea, Liliana del Carmen. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología. Centro Internacional de Estudios Avanzados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina